2017
DOI: 10.1177/2048872617724269
|View full text |Cite
|
Sign up to set email alerts
|

Editor’s Choice - Acute Cardiovascular Care Association Position Paper on Intensive Cardiovascular Care Units: An update on their definition, structure, organisation and function

Abstract: Acute cardiovascular care has progressed considerably since the last position paper was published 10 years ago. It is now a well-defined, complex field with demanding multidisciplinary teamworking. The Acute Cardiovascular Care Association has provided this update of the 2005 position paper on acute cardiovascular care organisation, using a multinational working group. The patient population has changed, and intensive cardiovascular care units now manage a large range of conditions from those simply requiring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 56 publications
0
47
0
6
Order By: Relevance
“…6 In light of such changes, expert groups from international professional societies have identified a need for CICUs to adapt to this transformation of cardiac critical care and called for additional research to quantitatively characterize the demographics, diagnoses, therapies, technology, and outcomes in contemporary CICUs to aid in directing such redesigns. 1,7,8 Additionally, experts have identified gaps in the evidence guiding the organization of CICUs as well as the management of the highly morbid conditions encountered in these units. 1,9,10 Despite the substantial resource consumption and heightened risk of many conditions requiring CICU care, to our knowledge, there are few highquality prospective studies and randomized clinical trials to guide practice in this environment.…”
mentioning
confidence: 99%
“…6 In light of such changes, expert groups from international professional societies have identified a need for CICUs to adapt to this transformation of cardiac critical care and called for additional research to quantitatively characterize the demographics, diagnoses, therapies, technology, and outcomes in contemporary CICUs to aid in directing such redesigns. 1,7,8 Additionally, experts have identified gaps in the evidence guiding the organization of CICUs as well as the management of the highly morbid conditions encountered in these units. 1,9,10 Despite the substantial resource consumption and heightened risk of many conditions requiring CICU care, to our knowledge, there are few highquality prospective studies and randomized clinical trials to guide practice in this environment.…”
mentioning
confidence: 99%
“…ECMO may offer an appealing support as this technique proved its efficacy in CS, 7 especially in the case of biventricular dysfunction. However, ECMO is available only in selected “level 3” centres, 8 limiting its utilization in routine. In our study, ECMO utilization mainly increased in large centres with cardiac surgery that may correspond to those “level 3” centres.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study showed an increase in the prevalence of CS in intensive care (from 4.1% to 7.7% between 1997 and 2012) [22], and persistence of a high mortality rate, advocating further specific research [13,16,22]. Moreover, little is known about networks dedicated to CS, despite the fact that they could play a major role in the management of these patients [23].…”
Section: Introductionmentioning
confidence: 86%